Work engagement and associated factors among healthcare professionals in the post-pandemic era: a cross-sectional study - Wang, Yiya; Tang, Li; Li, Lezhi (Frontiers in Public Health, 2023)
Background: With the shift of strategy in fighting COVID-19, the post-pandemic era is approaching. However, the "hard times" for healthcare systems worldwide are not yet ending. Healthcare professionals suffer negative impacts caused by the epidemic, which may seriously threaten their work motivation, concentration, and patient safety.Objective: Investigating the status and factors associated with Chinese healthcare professionals' work engagement in the post-pandemic era.A cross-sectional study was conducted to investigate healthcare professionals from ten hospitals in Hunan Province.